Dayak Iban Sebaruk Weanıng Ikat As Local Wısdom In Implementıng Character Educatıon In Students Of SMP Negerı 2 Sekayam - Eka Jaya Putra Utama; Nunik Esti Utami; Muhammad Sadikin (Cita Konsultindo Research Center, 2024)
The research aims to determine Dayak Iban Sebaruk ikat weaving as local wisdom in cultivating character education for students at SMP Negeri 2 Sekayam. Qualitative descriptive research with a single case study strategy, with data collection through direct observation, interviews and document study. Testing data validation through method triangulation techniques and source triangulation. Interactive data analysis starting from data collection, data reduction, data presentation and data verification. The results of the research show that the existence of the Dayak Iban Sebaruk people is not only based on agriculture but they are able to express their cultural arts in the form of weaving. Dayak ikat weaving has aesthetic, philosophical and economic value. The inheritance of weaving has been passed down from generation to generation by women until now. Local wisdom becomes a force to shape national identity. Cultural inheritance and local wisdom give rise to norms, ethics and customs which are used as capital to form students with character.